A survey of carbon stars in the Small Magellanic Cloud. - Morgan, D. H.; Hatzidimitriou, D. (1995)
A survey of carbon stars in the outer parts of the Small Magellanic Cloud has been completed; the candidate objects were identified by inspecting UK Schmidt Telescope objective-prism plates which cover a total area of ~220sq.deg on the sky, including the inter-Cloud region. Co-ordinates, accurate to =~2arcsec, are given for 1185 newly identified carbon stars. The spatial distribution of the SMC carbon stars appears to be identical to that of red, horizontal-branch/clump stars found by Gardiner & Hatzidimitriou (1992).
Keywords: MAGELLANIC CLOUD; STARS: CARBON SURVEYS